A case of recurrent pigmented macules in Laugier-Hunziker syndrome treated using a Q-switched Nd-YAG laser. (17th November 2019) - Choi, Myoung Eun; Jung, Chang Jin; Lee, Woo Jin; Won, Chong Hyun; Chang, Sung Eun; Lee, Mi Woo; Choi, Jee Ho; Paik, Seung Hwan
ABSTRACT: Laugier-hunziker syndrome (LHS) is a sporadic and acquired melanotic pigmentation of lips and oral mucosa which is not associated with gastrointestinal hamartomas in contrast to Peutz-Jeghers syndrome. Treatment using Q-switched neodymium: yttrium-aluminum-garnet (QS-ND:YAG) laser, Q-switched alexandrite laser and, cryotherapy have been reported. However, to the best of our knowledge, there is no report regarding long-term follow-up for recurrence. Herein we report the clinical features and the treatment of recurrent pigmented lesions in LHS patients. A patient diagnosed with LHS seven years ago presented with recurrent labial macules. She had undergone QS-ND:YAG laser 7 years ago and the labial macules have been gone several years. A physical examination revealed the macules were mainly on new locations and the spots on the site where the laser was previously done rarely recur. The untreated pigmented macules on gum were maintained in the same shape for seven years. Recurrent lesions of the lips and previously untreated macules on the gums were successfully treated again with the QS-ND:YAG laser as done in 7 years ago. Our case shows a long-term clinical course of laser-treated labial macules in LHS and treatment response of recurred lesions.